Non-coding RNAs repressive role in post-transcriptional processing of RUNX2 during the acquisition of the osteogenic phenotype of periodontal ligament mesenchymal stem cells - Assis, Rahyza I.F.; Feltran, Geórgia da S. [UNESP]; Silva, Maria Eduarda Salomão; Palma, Iasmin Caroline do Rosário; Rovai, Emanuel Silva; Miranda, Taís Browne de; Ferreira, Marcel Rodrigues [UNESP]; Zambuzzi, Willian F. [UNESP]; Birbrair, Alexander; Andia, Denise C.; da Silva, Rodrigo A. (Elsevier, 2021)
Mesenchymal stem cells are candidates for therapeutic strategies in periodontal repair due to their osteogenic potential. In this study, we identified epigenetic markers during osteogenic differentiation, taking advantage of the individual pattern of mesenchymal cells of the periodontal ligament with high (h-PDLCs) and low (l-PDLCs) osteogenic capacity. We found that the involvement of non-coding RNAs in the regulation of the RUNX2 gene is strongly associated with high osteogenic potential. Moreover, we evaluated miRs and genes that encode enzymes to process miRs and their biogenesis. Our data show the high expression of the XPO5 gene, and miRs 7 and 22 observed in the l-PDLCs might be involved in acquiring osteogenic potential, suppressing RUNX2 gene expression. Further, an inversely proportional correlation between lncRNAs (HOTAIR and HOTTIP) and RUNX2 gene expression was observed in both l- and h-PDLCs, and it was also related to the distinct osteogenic phenotypes. Thus, our results indicate the low expression of XPO5 in h-PDLC might be the limiting point for blocking the miRs biogenesis, allowing the high gene expression of RUNX2. In accordance, the low expression of miRs, HOTAIR, and HOTTIP could be a prerequisite for increased osteogenic potential in h-PDLCs. These results will help us to better understand the underlying mechanisms of osteogenesis, considering the heterogeneity in the osteogenic potential of PDLCs that might be related to a distinct transcriptional profile of lncRNAs and the biogenesis machinery.
Keywords: Epigenetic background; Osteogenic potential; Periodontal regeneration; Stem cells; Tissue engineering